1997
DOI: 10.1021/jf970070y
|View full text |Cite
|
Sign up to set email alerts
|

Solubility−Digestibility Relationship of Legume Proteins

Abstract: Protein solubility of raw and cooked faba bean, lentil, chickpea, and dry bean was tested in water and in NaCl in the pH range 1.0−13.0. The solubility of all legume proteins in water typically increased on both sides of pH 4.0. In NaCl, only solubility of raw dry bean proteins was improved. A marked reduction in protein solubility was observed after cooking of all legumes up to pH 10.0, where solubilization occurred, suggesting that it was dependent on deprotonation of lysine and arginine. Amino acid analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
152
0
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(184 citation statements)
references
References 34 publications
25
152
0
7
Order By: Relevance
“…An analysis of variance revealed that all isolates displayed significantly different (p<0.05) solubility values, which were found to be the highest for CPI (~94 %), followed by LPI (~90 %), FPI (~85 %) and SPI (~50 %). Similar solubility for legume protein isolates prepared by isoelectric precipitation has been reported in literature for CPI (>80 %) by Sánchez- Vioque et al (1999), and for CPI, FPI and LPI (all >80 %) by Carbonaro et al (1997). Solubility is mediated by the balance of proteinprotein and protein-solvent (aqueous phase) interactions, the latter promoting solubility, which can further be influenced by environmental factors (e.g., temperature, pH, ionic strength) (McClements 2007;Can Karaca et al 2011) and by processing (e.g., extraction or post-extraction treatments) (Kinsella 1979).…”
Section: Protein Solubilitysupporting
confidence: 84%
See 1 more Smart Citation
“…An analysis of variance revealed that all isolates displayed significantly different (p<0.05) solubility values, which were found to be the highest for CPI (~94 %), followed by LPI (~90 %), FPI (~85 %) and SPI (~50 %). Similar solubility for legume protein isolates prepared by isoelectric precipitation has been reported in literature for CPI (>80 %) by Sánchez- Vioque et al (1999), and for CPI, FPI and LPI (all >80 %) by Carbonaro et al (1997). Solubility is mediated by the balance of proteinprotein and protein-solvent (aqueous phase) interactions, the latter promoting solubility, which can further be influenced by environmental factors (e.g., temperature, pH, ionic strength) (McClements 2007;Can Karaca et al 2011) and by processing (e.g., extraction or post-extraction treatments) (Kinsella 1979).…”
Section: Protein Solubilitysupporting
confidence: 84%
“…1), which may have contributed to its reduced solubility. However, solubility of proteins is influenced by other factors, such as salts, conformation, pH, level of association/disassociation and hydrophobicity (Carbonaro et al 1997;McClements 2004;Damodaran 2005). In general, proteins that have higher surface hydrophobicity tend to be negatively correlated to solubility (Can Karaca et al 2011), however in the present study, CPI showed both the highest solubility and surface hydrophobicity which reflects the complexity behind fully understanding the structure-function mechanism related to solubility.…”
Section: Protein Solubilitymentioning
confidence: 60%
“…Digestibilidad in vitro La FRP de chı´a presento´una digestibilidad in vitro de 77,53%, superior a la reportada para harinas de garbanzo con 75,2% (Sa´nchez-Vioque, Clemente, Vioque, Bautista, & Millan, 1999); harina de frijol negro (Phaseolus vulgaris) con 73,8% (Carbonaro, Cappelloni, Nicoli, Lucarini, & Carnovale, 1997) y para harina de frijol lima (P. lunatus) con 72,4% (Betancur-Ancona et al, 2004b), pero inferior a la reportada para aislado proteı´nico de garbanzo con 95,6% (Sa´nchez-Vioque et al, 1999), lo cual muestra que las proteı´nas como se menciono´antes, pudieron haber sufrido una desnaturalizacio´n durante el desgrasado. No se tienen reportes de factores no nutritivos en la chı´a, con lo cual se puede descartar la presencia de inhibidores de proteasas que pudieran retardar la digestibilidad in vitro, aunque sı´hay reportes de la presencia de compuestos feno´licos antioxidantes como ya se demostro´, que se sabe pueden disminuir el aprovechamiento de las proteı´nas (Siddhuraju & Becker, 2001).…”
Section: Determinacio´n De Aminoa´cidosunclassified
“…A digestibilidade in vitro da proteína total de grão-de-bico, em diferentes genótipos, mostra uma variação entre 60,4 e 74,4% [2,11], e aumento variável de 68,6 a 77,5% foi observado em diferentes cultivares após descorticação e/ou cozimento [4,7,20]. Essa digestibilidade protéica tem sido melhorada em função de tratamentos, tais como: germinação, fermentação, aquecimento, descorticação, entre outros [9,27].…”
Section: -Introduçãounclassified